Analisis Hukum Terhadap Sengketa Kepemilikan Tanah di Perdesaan Bersertifikat Ganda - Cepi Winarso; Nathasya Nathasya; Santy Fitnawati WN; Robby Nurtresna (International Forum of Researchers and Lecturers, 2024)
Land ownership was part of the civil rights, and the state gave legal evidence to probed peoples with land certificates. Inaccuracies in the making of the land papers/certificates could be due to deliberate or fraud (fraud) and/or coercion (dwang) in the making of the physical or legal data recorded on the land list. Hence, the certificate given may be invalid. The purpose of this research is to 1. Analyzing how the settling of the overlapping land-ownership disputes led to a dual certificate. 2. BPN responsibility analysis and legal protection methods in the making of double certificates. The study is conducted using a methodological study of prescriptive law and a field investigation approach. The land dispute was a dispute between two or more persons to retain a legal property rights against each person or group to maintain an interest in the same land or item inside or above the ground.